Adding zeolite to multi-component fine-grain concrete used for 3D construction printing - A. D. Kogai; A. V. Puzatova; M. A. Dmitrieva; V. N. Leitsin (Vestnik MGSU)
Introduction. Requirements, applied to materials used for 3D construction printing, can be met by adding modifiers at the stage of designing fine-grained concrete compositions. Natural zeolites can be considered highly effective finely dispersed additives capable of adjusting properties of concrete mixtures, that are particularly relevant for remote development areas having deposits of this mineral raw material.Materials and methods. Research works and experimental data are reviewed to analyze the use of zeolites as a mineral additive in construction. Zeolites can partially, to different extents, replace cement in concrete to optimally meet the requirements of construction 3D printing. The setting time, the density and the dynamic shear stress of various compositions of concrete mixtures, as well as the density, ultimate compressive and bending strength values were determined for mature concrete. Results of strength and calorimetric testing were used to evaluate the activity of zeolite.Results. The best performance was demonstrated by the specimens with 5–15 % zeolite content by the cement weight. The information is provided about the time it takes for the density of concrete mixture to become critical to ensure its suitability for a 3D printer, which is reduced by 60 to 80 minutes for compositions with the 5–15 % zeolite content compared to the controlling composition, provided that and the mixture suitability period can be optimized by choosing the concentration of zeolite. The initial density of the concrete mixture, evaluated using the Vicat cone penetrometer, did not demonstrate any great changes when the share of zeolite was increased.Conclusions. Zeolite improves mechanical characteristics of fine-grained concrete and adjusts the setting time depending on the concentration of the mineral filler. Hence, zeolite can be considered as an effective component of concretes suitable for additive technologies.